2021
DOI: 10.1088/1757-899x/1073/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Developing vocabulary card base on Augmented Reality (AR) for learning English

Abstract: The application of technology in the world of education can affect the quality of students in understanding learning material because technology is one of the important elements to assist in the teaching and learning process. One educational application that can be developed is Augmented Reality (AR) technology. AR is one of the learning media that can be used to combine virtual objects or objects into a real environment with the virtual world to be able to interact in realtime. English is a foreign language t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…AR flip card for learning English [18]. The study used a multimodal technology in which the data were analyzed qualitatively.…”
Section: Classification Advantages Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…AR flip card for learning English [18]. The study used a multimodal technology in which the data were analyzed qualitatively.…”
Section: Classification Advantages Limitationsmentioning
confidence: 99%
“…Along similar lines, mobile-based applications help in creating an effective English environment for EFL students because they play a pivotal role in facilitating their English language acquisition [17]. Moreover, a mobile-based AR application improves students' English vocabulary and creates a positive and attractive learning atmosphere [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has closely examined the effect of AR on students' motivation and engagement and found that it was greatly increased [36]. Studies have also demonstrated that AR increased learning performance and positive attitudes towards language learning [37][38][39], as well as high levels of word retention and vocabulary development [40][41][42][43]. Another significant advantage of AR over any other educational tools is that it allows for authentic, meaningful communication and interaction among peers and their teachers in the target language, based on real-life situations [44].…”
Section: Game-based Learning and Ar In Educationmentioning
confidence: 99%
“…Chen and Chan (2019) demonstrated that AR technology can improve vocabulary learning in kindergartens and expand children's vocabulary. Rozi et al (2021) state that AR will make learning English vocabulary more attractive and argue that it can help students remember and learn vocabulary.…”
Section: Augmented Reality and English Learningmentioning
confidence: 99%